Remain : a supernatural love story - Sparks, Nicholas; Shyamalan, M. Night (Random House, 2025)
After a stay in a psychiatric facility for depression, New York architect Tate Donovan heads to Cape Cod to design his best friend's summer home and start over. Still haunted by his sister Sylvia's death-- and her unsettling claim that their family can see spirits--Tate tries to ground himself in logic and work. But everything changes when he meets Wren, a captivating young woman whose warmth and mystery draw him in instantly. As their connection deepens, Tate begins to sense that something dark lies beneath Wren's seemingly perfect small-town life. To save her-- and himself-- he must uncover the truth about her past and confront questions that blur the line between the living and the dead. A haunting and emotional story about love, loss, and the thin veil that separates reality from the unseen.